2014
DOI: 10.1017/s136672891400011x
|View full text |Cite|
|
Sign up to set email alerts
|

Gender conflict resolution in Spanish–Basque mixed DPs

Abstract: This study analyzes gender assignment in Spanish–Basque mixed nominal constructions with nouns in Basque (a language that lacks gender) and determiners in Spanish (a language that marks gender) by using a multi-task approach: (i) naturalistic data, (ii) an elicitation task, and (iii) an auditory judgment task. Naturalistic data suggest cross-language effects under which a morphological marker of Basque (-a determiner) is interpreted as a morphophonological expression of gender marking in Spanish. A preference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 25 publications
0
14
0
10
Order By: Relevance
“…Similarly, community differences in the preferred pattern of use in code-switching can and should arise because the specific structure that a community adopts may be influenced by a host of linguistic and extra-linguistic variables. Valdés Kroff (2016) found that Spanish-English bilinguals in Miami use predominantly masculine gender in mixed nominal constructions, and recent research indicates that Spanish-Basque code-switching has settled on the use of feminine-marked mixed nominal constructions as the dominant pattern (Parafita Couto et al, 2015b). Subsequently, Valdés Kroff (2016) argues that the predictions for online processing of gender should be different between Spanish-Basque and Spanish-English bilinguals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, community differences in the preferred pattern of use in code-switching can and should arise because the specific structure that a community adopts may be influenced by a host of linguistic and extra-linguistic variables. Valdés Kroff (2016) found that Spanish-English bilinguals in Miami use predominantly masculine gender in mixed nominal constructions, and recent research indicates that Spanish-Basque code-switching has settled on the use of feminine-marked mixed nominal constructions as the dominant pattern (Parafita Couto et al, 2015b). Subsequently, Valdés Kroff (2016) argues that the predictions for online processing of gender should be different between Spanish-Basque and Spanish-English bilinguals.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this default status, such an outcome in code-switching reflects a choice made by the speech community. For example, other researchers have noted that Spanish in contact with Basque — a language that, like English, lacks grammatical gender — settles on the use of the feminine determiner as the preferred, default article in Spanish-Basque code-switching (Parafita Couto, Munarriz, Epelde, Deuchar, & Oyharçabal, 2015). Given the findings here, we would predict that for Basque-Spanish bilingual communities, gender would also be processed in an asymmetric manner in code-switched sentences, but now with the masculine determiner reliably affording opportunities for facilitated processing.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless other studies find a strong tendency for transferred nouns to be allocated to a default category, suggesting that loanwords are not always treated the same as native nouns. For example, in Spanish-Basque code-switching, where bilingual noun phrases consist of a Basque noun and Spanish articles, bilinguals show a preference for feminine articles (regardless of the gender of the translation equivalent) (Parafita Couto et al, 2015). In Maltese, 86% of a sample of 94 English nouns were borrowed into the masculine gender, regardless of their phonology and the fact that Maltese has a largely formal system of gender assignment (Stolz, 2009: 335).…”
Section: Transferring Gender-less Nouns In a Language With Gendermentioning
confidence: 99%
“…Most of this work has examined code-switching and borrowing contexts where noun transfer has occurred between a language which marks gender and one which does not mark gender. Some of these studies have investigated situations where nouns from a language with no gender have transferred into a language with a gender system, with a particular eye on the principle(s) underlying the gender categorisation of transferred nouns (Deuchar et al, 2014;Jake et al, 2002;Liceras et al, 2008;Parafita Couto et al, 2015;Poplack et al, 1982). Other studies have examined instances of nouns from a language with a gender system which have transferred into a language without one, and the ramifications for the recipient language, i.e.…”
Section: Introductionmentioning
confidence: 99%